2009
DOI: 10.1039/b821559f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of acid–base catalysis in the extradiol and intradiol catechol dioxygenase reactions using a broad specificity mutant enzyme and model chemistry

Abstract: The extradiol and intradiol catechol dioxygenase reaction mechanisms proceed via a common proximal hydroperoxide intermediate, which is processed via different Criegee 1,2-rearrangements. An R215W mutant of extradiol dioxygenase MhpB, able to produce a mixture of extradiol and intradiol cleavage products, was analysed at pH 5.2-8.6, and the yield of extradiol product was found to be highly pH-dependent, whereas the yield of intradiol product was pH-independent. The acid-base chemistry of a biomimetic reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Such a transition results in the displacement of Tyr-253 and a water molecule, which leads to the deprotonation of the hydroxyl group of 3-MC, as well as the provision of a position for an oxygen molecule. This proposed process is in a good agreement with previous reports that the oxygen interaction occurs after the binding of the catechol substrate during the catalytic process of extradiol dioxygenases (3)(4)(5)(6)(7). In summary, this work shows that ring cleavage by the DK17 AkbC enzyme is preceded by a series of substrate-positioning steps, such that the flexible motifs direct and correctly position the substrate into the binding pocket/active site, allowing efficient substrate catalysis and product release.…”
Section: Discussionsupporting
confidence: 81%
“…Such a transition results in the displacement of Tyr-253 and a water molecule, which leads to the deprotonation of the hydroxyl group of 3-MC, as well as the provision of a position for an oxygen molecule. This proposed process is in a good agreement with previous reports that the oxygen interaction occurs after the binding of the catechol substrate during the catalytic process of extradiol dioxygenases (3)(4)(5)(6)(7). In summary, this work shows that ring cleavage by the DK17 AkbC enzyme is preceded by a series of substrate-positioning steps, such that the flexible motifs direct and correctly position the substrate into the binding pocket/active site, allowing efficient substrate catalysis and product release.…”
Section: Discussionsupporting
confidence: 81%
“…We rule out the former which gives aN and aHβ values larger than those of the latter 25,26 . Since the other oxygen-centered radicals were not observed experimentally, these two radicals were probably not released from the intra-(at C1-C2 site) or extra-diol (at C1-C6 site) cleavages which was similar to those in catalysis by catechol dioxygenase or in chemical oxidation 20,21,[27][28][29][30][31][32] . Therefore, the trapped non-aromatic carbon-centered radical was assigned to the isomer of the o-benzosemiquinone radical, which was also detected in HPLC-MS ( Fig.2e).…”
Section: Resultsmentioning
confidence: 93%
“…Obviously, the formed obenzosemiquinone radical alone does not yield any adduct product. When adding laccase, a chelate complex was formed between the o-benzosemiquinone radical and the counterion Cu 1+ / Cu 2+ (T1) [19][20][21][27][28][29][30][31][32] . The inductive effect caused by Cu ion activates the cation radical tendency at the C4-C5 site.…”
Section: Resultsmentioning
confidence: 99%
“…The pH was found to influence the activity of catechol 1,2-dioxygenase. Brivio et al [26] found that catechol 1,2-dioxygenase activity is independent of pH, in the pH range of 5.2–8.6. Silva et al [27] reported that catechol 1,2-dioxygenase activity was very low when pH value equaled to 4.…”
Section: Resultsmentioning
confidence: 99%